Peran Kepala Desa Dalam Menanggulangi Kenakalan Remaja di Desa Labuan Kecamatan Labuan Kabupaten Pandeglang - E. Nita Prianti; Ismi Rumiyati (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research was conducted in the village of Labuan, Labuan sub-district, Pandeglang Regency. with the aim of 1) To find out the Role of the Village Head Against Juvenile Delinquency in Labuan Village, Pandeglang Regency. 2) To find out the factors that influence juvenile delinquency in Labuan Village, Pandeglang Regency. 3) To find out the efforts in tackling juvenile delinquency in Labuan Village, Pandeglang Regency. The method used is a qualitative method with data collection through observation techniques, interviews and documentation. The analysis used is to use triangulation with data reduction techniques, data display and data verification. The results obtained in this study are that the role of the Labuan village head in Pandeglang district in tackling juvenile delinquency is quite good. According to the results of the data that the researchers obtained, the Labuan village head had carried out his obligations in carrying out his duties as an obligation. The village head has tried to minimize juvenile delinquency through an appeal to always be aware of its citizens, cooperate in participating in positive things, set a positive example, appreciate what teenagers do and provide sanctions according to irregularities committed for the perpetrators.